Élhetőbb város - avagy Smart City = Smart Cities for a better world - Ritó, Evelin (Közép-Európai Közlemények, 2018)
The subject of this essay is the topic of Smart City, which is one of the important areas of the ongoing European integration. The internet and digital technologies are transforming our world in every walk of our private and commercial lives. Cities must take an active part in the digital revolution, and must make all the resulting new digital possibilities available to all citizens and enterprises. In the field of digital tools and service there are multiple untapped opportunities that await citizens and enterprises. From online purchase and learning through paying the checks to online administration, the web offers the best solution, if conditions are provided. Nowadays we are witnessing the time of social changes, scientific discoveries and the rapid development of technology. This process is accompanied by the incursion of “civilization”, the increase of the standard of living and life expectancy and the rising number of the Earth’s population. The latter goes hand in hand with the growing number of cities and their growing size as well. Today more than half of the Earth’s population lives in cities. In the early 21st century the number of urban habitants surpassed 50% of the entire human population. By the end of the century this ratio will expectedly be 70–75%. This not only shows the importance of cities but also the responsibility and challenge that urbanization means all around the world. Through my research I attempt to make Smart City the subject of this essay, as more than half of the Earth’s population is living in cities as the result of the increasingly fast urbanization. The coexistence and environmental change pose new challenges to the inhabitants and leaders of urban areas in many areas of life. Urban development and operation can increasingly be realized only through up-to-date and effective tools. The info-communicational solutions, which are becoming increasingly integral to urban life, add effectively and with a lower cost to the perceptible increase in the quality of life, while invigorating the community’s economy on a local and national level. The goal of my research is to review the related works of Hungarian and international authors in order to make a comprehensive analysis of this area, which in my opinion is exceedingly important, as smart technology is an integral part of our daily lives.